Interaction design in distributed software development: a systematic mapping study - Domingos Alves, Daniel; Souza Matos, Ecivaldo de; Chavez, Christina von Flach G. (Behaviour & information technology, 2024)
Context: Interaction design has been consolidated as a practice with potential to support interactive systems projects. Most interaction design solutions (methods, techniques, and tools) have been created to be used in environments with co-located participants. However, the number of software projects that are developed in environments with geographically distributed stakeholders has increased. Despite some research efforts, little is known about how the scientific literature has addressed interaction design in distributed software development (DSD). Objective: To provide an overview of studies that have been conducted on interaction design in DSD. Method: A systematic mapping study was conducted to identify, synthesise and analyse papers related to interaction design in DSD, and 32 papers were included and classified in relation to the research type and research topic. Results: Through the analysis of the included papers, this paper provides an overview of existing interaction design studies in the context of DSD. This paper presents an analysis of the main characteristics of interaction design in DSD, such as the level of dispersion of stakeholders, the solutions adopted (approaches, methods, techniques, tools), the involvement of end users, and the performance of designers and HCI specialists. We have identified gaps and a taxonomy of six research topics. The findings of this study also allowed us to propose an agenda for future research on distributed interaction design. Conclusion: This paper contributes to the body of knowledge of interaction design at the frontier of research between HCI and DSD by (i) providing an overview of research efforts on interaction design in DSD, (ii) presenting an overview of how interaction design has been conducted in DSD projects, and (iii) identifying research gaps and discuss future research directions emerged from the study.